Effects of neoclassical tearing modes and toroidal field ripple on lost alpha power in the SPARC tokamak. (1st December 2022) - Braun, A E; Kramer, G J; Tinguely, R A; Scott, S D; Sweeney, R M
Abstract: Using the SPIRAL Monte Carlo, full particle-orbit simulation code, we investigate the effects of neoclassical tearing modes (NTMs) and toroidal field (TF) ripple on alpha power losses during steady-state operation of the SPARC primary reference discharge. Model perturbations for TF ripple and the m / n = 2 / 1 and 3 / 2 NTMs with exaggerated widths selected based on an H-mode plasma approaching thermal quench are added to a simulated SPARC magnetic equilibrium through which marker particles are tracked. The 3/2 and 2/1 NTMs are located at ρ p o l ∼ 0.76 and ρ p o l ∼ 0.86 respectively, well positioned to increase alpha particle transport into and within an outer lossy region of the plasma beyond ρ p o l ∼ 0.8 where over 95% of lost alpha particles are born. Total alpha power losses are shown to increase modestly from 1.73% lost at a minimum to 2.34% lost at a maximum, and alpha particle surface power densities form localized hotspots on the first-wall near the low-field side midplane due to NTMs and TF ripple. We establish a conservative upper limit for first-wall alpha surface power densities on a toroidally symmetric wall for typical, flattop operation and motivate the consideration of NTMs in the design of three dimensional limiter surfaces for SPARC.